Improving Tree-based Pipeline Optimization Tool with Geometric Semantic Genetic Programming - Chhotobhai, Helena Hetal (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Data Science